The static allometry of sexual and nonsexual traits in vervet monkeys. (30th December 2014) - Rodríguez, Rafael L.; Cramer, Jennifer Danzy; Schmitt, Christopher A.; Gaetano, Tegan J.; Grobler, J. Paul; Freimer, Nelson B.; Turner, Trudy R.
<x xml:space="preserve">Abstract</x> Sexual traits vary tremendously in static allometry. This variation may be explained in part by body size‐related differences in the strength of selection. We tested this hypothesis in two populations of vervet monkeys, using estimates of the level of condition dependence for different morphological traits as a proxy for body size‐related variation in the strength of selection. In support of the hypothesis, we found that the steepness of allometric slopes increased with the level of condition dependence. One trait of particular interest, the penis, had shallow allometric slopes and low levels of condition dependence, in agreement with one of the most consistent patterns yet detected in the study of allometry, namely that of genitalia exhibiting shallow allometries. © 2014 The Linnean Society of London, Biological Journal of the Linnean Society, 2015, 114, 527–537.